Pharmacognostic standardisation and phytochemical analysis of Tetracera akara (Burm. f.) Merr. - Ragesh R Nair; S R Suja; V Vilash; A L Aneeshkumar; S Rajasekharan (Journal of Traditional and Folk Practices (JTFP), 2016)
Tetracera akara (Burm. f.) Merr. (Dellineaceae) is used by the Kani tribe of Kerala, India for treating various liver ailments. The plant has pharmacologically active compounds namely Betulin, Betulinic acid, Lupeol and β-Sitosterol possess anti-HIV, anti-diabetic and anti-inflammatory potential. However, there is no data available regarding the pharmacognostic standardization of this plant. Therefore, the aim of the present study was to standardize the pharmacognostic features of T. akara root by physicochemical characterisation, morpho-anatomical studies of various plant parts and detailed phytochemical studies by HPTLC profiling. The pharmacognostic evaluation of T. akara revealed the presence of characteristic morphological, organoleptic and physicochemical features of the plant. The anatomical studies helped to distinguish root and stem material even in crushed or powdered form. Detailed leaf anatomy showed the presence of uniseriate trichomes with tapered end and paracytic stomata on the lower leaf surface. Powder analysis of root showed the presence of calcium oxalate and raphide crystals, xylem fibre, vessel and tracheids. Preliminary phytochemical analysis of crude extract of T. akara revealed the presence of phytoconstituents like flavonoids, phenols, tannins, saponins and terpenoids. HPTLC studies of crude extract and ethanolic fraction revealed the comparative HPTLC fingerprinting profile of T. akara at 254 and 366nm for the first time. The present investigation thus sets a benchmark in authenticating the genuine plant material by setting diagnostic indices for the identification and preparation of monograph of T. akara, a new entry in the field of therapeutics.